Faktor – faktor yang Berhubungan dengan Kebersihan Gigi dan Mulut pada Lansia - Aisyah AR; Hasrini Hasrini; Amirah Maritsa; Zahrawi Astrie Ahkam; Fidzah Nurfajrina Murad; Arfiah Jauharuddin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
The lack of oral hygiene become a problem for elderly. The main aims of this research is to analyze the related factors due to oral hygiene consists of age, sex, education degree, occupation, marital status, knowledge, motivation, physical dependence, culture, anxiety, economic of family and elderly. The design of this research were descriptive analytic and cross sectional. UPTD Puskesmas I Penebel was the location where this research was conducted. Purposes sampling technique was used with the total samples where 80 respondents. The results showed the significant correlation between oral hygiene and knowledge (p value 0,013, r = 0,277), motivation (p value 0,005, r = 0,311), physical dependence (p value 0,011, r = 0,285), economic of family and elderly (p value 0,0000, r = 0,400), anxiety (p value 0,0185, r = -0,265). There was no correlation between culture and oral hygiene (p value 0,187, r = -0,149). Based on this research, it is recomended that oral hygiene supposed to be clearly informed to elderly by elderly posyandu (integrated treatment) activities, and regularly oral hygiene checkup which is integrated in puskesmas (civic health Centre).